Nutritional regime effects on quality and yield characteristics of beef - Harrison, A.R.; Smith, M.E.; Allen, Dell M.; Hunt, Melvin C.; Kastner, Curtis L.; Kropf, Donald H. (American Society of Animal Science, 2008)
Quality and yield characteristics of 38 crossbred steer carcasses were evaluated to measure the effects of four nutritional regimes: grass-fed -- winter growing ration (2.18 Mcal ME/kg), followed by summer grazing; short-fed = same as grass-fed, followed by 49 days in drylot on a high grain ration (3.11 Mcal ME/kg); long-fed = same as short-fed, except fed 98 days in drylot; and forage-fed = same as grass-fed, followed by 98 days in drylot on a high forage ration (2.84 Mcal ME/kg). Higher marbling scores and quality grades and a whiter external fat resulted from increased feeding. Lean texture did not differ (P<[.05) among feeding regimes, but tended to be finer in longer fed cattle. Bone maturity increased over a 98-day feeding period, but remained well within the A maturity range. Longer feeding increased carcass weight, fat thickness, ribeye area, internal fat and numerical yield grade and reduced cooler shrinkage. All taste panel responses (tenderness, desirability of flavor of lean and fat and juiciness) to longissimus samples favored longer fed beef. Generally, nutritional regime did not affect shear force measurement, however, some differences in shear force were noted in biceps femoris muscle. Carcasses from cattle fed the longest time and the highest plane of nutrition had the most desirable quality and palatability characteristics. This study indicates that carcasses from cattle fed a high quality ration for a certain period of time will be of acceptable palatability regardless of marbling level or availquality grade.
Keywords: Food science; Beef; Nutritional regimes; Quality; Yield